TINJAUAN YURIDIS PELANGGARAN HAK CIPTA ATAS FILM MELALUI APLIKASI MEDIA SOSIAL - Tiara Arfiana; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The development of technology, especially in the field of telecommunications and information that is sweeping the world today is inevitable. It is also undeniable, these developments affect the order, less balanced with a good and adequate understanding of technology, especially in a legal perspective.This type of research can be classified in the type of normative legal research, studying the legal principles contained in Law Number 28 of 2014 concerning Copyright. By its nature, this legal research is descriptive in nature, describing and describing all data obtained from the results of a literature study relating to the title of a legal writing that is clearly and in detail then analyzed to answer the problem under study.From the results of research and discussion it can be concluded that, First, the use of social media application services when screening films in the cinema can be categorized as copyright infringement on film or cinematography, because the use of these services violates moral rights and economic rights in which these rights are elements most important in copyright. The use of social media applications when screening films in theaters can be categorized as copyright infringement because of violations of moral rights, because the perpetrators do not retain the rights of the creator in the modification of the creation (film). Whereas in violation of economic rights, the perpetrators announce, duplicate, broadcast the work (film) without permission to the creator and use the service for commercial purposes. Second, the criminal liability of film piracy actors through social media applications is already contained in Law Number 28 of 2014 concerning Copyright specifically contained in Article 112 and Article 113, but the laws and regulations governing in detail and can ensnare perpetrators with criminal sanctions not yet available, because based on the provisions of this article the perpetrators of copyright infringement can be convicted if the action is taken for commercial gain.Keywords: Copyright - Film - Social Media